PENINGKATAN POTENSI DIRI MAHASISWA MELALUI KULIAH KEWIRAUSAHAAN - Susilogati, Sri; Wijayati, Nanik; Rengga, Dyah Pita (Lembaran Ilmu Kependidikan, 2008)
Students do not have much experience of entrepreneurship in the meantime. Itindicates their weakness of practical application toward community problem. Specificpurpose of this activity is to enhance studentÃ¢â¬â¢s self-potency through entrepreneurshipsubject in order to be a successful entrepreneur. The teaching methods of this subjectare lecturing, product-making, presentation, direct visit, and written test. Theentrepreneurship subject focuses on problem-solving of small industry. Givingcomprehension and a little experience will help to form their sincerity to start andmanage a business. Statistically, there is a significant difference in entrepreneurialspirit between the initial condition and final condition, either on the basis of selfassessment or peer assessment. Based on the result gained from this activity, it can beconcluded that studentÃ¢â¬â¢s self-potency can be enhanced through entrepreneurshipsubject. It is suggested to students of Semarang State University to keep on doingbusiness development to be a successful entrepreneur.Kata Kunci:Pengembangan, potensi, wirausaha